Age-dependent impact of new ESC-Guideline recommended door-to-balloon times on mid-term survival in acute ST-elevation myocardial infarction patients undergoing primary percutaneous coronary intervention. (1st November 2016) - Wang, Yu-Chen; Huang, Ying-Ying; Lo, Ping-Hang; Chang, Kuan-Cheng; Chen, Chu-Huang; Chen, Ming-Fong
Abstract: Background: To investigate the age-dependent impact of the superfast door-to-balloon (D2B) times of ≤ 60 min as recommended by the new ESC Guideline for patients with ST elevation myocardial infarction (STEMI) undergoing primary percutaneous coronary intervention (PPCI) on mid-term survival rates based on a single center registry dataset. Patients and methods: This study enrolled consecutive STEMI patients who underwent PPCI from Jan 1, 2009 through Sep 30, 2013. We compared demographics, clinical characteristics and the D2B-survival relationships between patients aged ≥ 65 and < 65. Results: The younger group comprised 242 patients (68%) aged < 65 and the elder group consisted of 115 patients (32%) aged ≥ 65. In patients aged < 65, the mortality rate decreased linearly with D2B time shortening (> 90 min vs. 61–90 min vs. ≤ 60 min = 14.9% vs. 13.3% vs. 1.2%, P = 0.001). Contrarily, shortening of D2B time was not associated with reduced mortality rate in patients aged ≥ 65 (> 90 min vs. 61–90 min vs. ≤ 60 min = 23.5% vs. 19% vs. 18.9%, P = 0.99). In younger patients but not the elderly, a D2B time of < 60 min has sufficient power to predict mortality with a sensitivity of 0.83, specificity of 0.74, and Youden index of 0.57. Conclusions: Our results show that the new ESC Guideline recommendation of D2B time ≤ 60 min is associated with better survival rates in younger STEMI patients undergoing PPCI. Our findings stress the importance of guideline adherence to minimize reperfusion delay to improve survival in these patients.